La riqueza de un territorio que ha vivido los avatares de la violencia (2016)
The article briefly describes the relation between the landmarks of the municipality of Quibdó (capital of the department of Chocó) and its impact on the conceptions of territory of its inhabitants, which allows reflecting on the implications for the territorial subject of aspects such as mining, illicit cultivation and violence, acts that have affected their own territorial history and which underlie feelings for the territory lived, transformed, subjected and abused.